Working Towards Math Facts Mastery - Durham, Anne (Journal of the American Academy of Special Education Professionals, 2012)
Fluency in math facts is essential if students are going to be able to work through more complex math processes with ease. Most of my special education students arrived at middle school with limited skills. To help them achieve mastery with their multiplication and division facts, the intervention described in the article was conducted. Most of the students showed significant improvement in their abilities. The data shows the before and after positions of each student and discusses possible reasons why most did not develope these necessary skills while still in elementary school.